MEDIA PEMBELAJARAN PENGENALAN SUARA HEWAN BERBASIS ANDROID DI TK PERTIWI BORONGGANJENG - Nur Asima; Dedy Hendryadi; Andi Nurul Faizah (journal Informatika, Multimedia, dan Informasi, 2023)
This study aims to: (1) design a learning media application for animal speech recognition, especially for TK Pertiwi Borongganjeng using android. (2) implementing an android-based animal voice recognition learning media application at Pertiwi Borongganjeng Kindergarten. (3) increase knowledge and interest in learning for students in learning Animals or Animals, especially knowing the surrounding environment. This study uses the Multimedia Development Life Cycle (MDLC) method. This multimedia development model consists of six stages, namely concept, design, collecting material, assembly, testing, and distribution. From the results of data processing and discussion conducted, this research resulted in the conclusion that the learning media created can increase interest in learning and increase student knowledge and can be implemented. Based on this research, using an instrument in the form of a questionnaire to determine the success rate of application and student learning. Then on the aspect of student knowledge, it can be known by giving a quiz after using the application. From the questionnaire that was distributed after using the application, an average of 53% was obtained in the "Medium" category. This shows that students' interest in learning increases and students' knowledge increases. From these data, it can be concluded that the learning media made was successful and could increase students' interest in learning and knowledge in learning animal voice recognition and can be used as a learning medium for animal voice recognition for TK Pertiwi Borongganjeng.